PENDEKATAN FENOMENOLOGIS DALAM HERMENEUTIKA SOSIAL: Studi atas Tafsir Kontekstual Hasan Hanafi - Rizky Ramadhan Sitepu (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
This article explores the phenomenological approach as a methodological framework with in Islamic studies, capable of uncovering religious experiences in a profound and contextual manner. In contemporary Islamic scholarship, phenomenology contributes significantly to understanding the spiritual, cultural, and social dynamics of Muslim communities by emphasizing the importance of subjective experience and the meanings that emerge from lived religious realities. The author specifically examines the thought of Hasan Hanafi, who integrates the phenomenological approach with social hermeneutics in interpreting the Qur’an. Through this approach, the interpretation of sacred texts extends beyond their literal meaning, taking into account the social and historical realities of the Muslim community. This study employs a qualitative method with a literature review approach, focusing on Hanafi’s thought as the primary object of analysis. The findings indicate that the phenomenological approach in Islamic studies can enrich religious understanding, contextualize religious messages, and offer an emancipatory interpretive framework that guides the liberation of the ummah through contextual hermeneutics.